Variability of Cost and Time Delivery of Educational Buildings in Nigeria (International Journal of Built Environment and Sustainability, 2017)
Cost and time overrun in construction projects has become a reoccurring problem in construction industries around the world especially in developing countries. This situation is unhealthy for public educational buildings which are executed with limited government funds, and are in most cases time sensitive, as they need to cater for the influx of students into the institutions. This study therefore assessed the variability of cost and time delivery of educational buildings in Nigeria, using a study of selected educational buildings within the country. A pro forma was used to gather cost and time data on selected building projects, while structured questionnaire was used to harness information on the possible measures for reducing the variability from the construction participants that were involved in the delivery of these projects. Paired sample t-test, percentage, relative importance index, and Kruskal-Walis test were adopted for data analyses. The study reveals that there is a significant difference between the initial and final cost of delivering educational buildings, as an average of 4.87% deviation, with a sig. p-value of 0.000 was experienced on all assessed projects. For time delivery, there is also a significant difference between the initial estimated time and final time of construction as a whopping 130% averaged deviation with a sig. p-value of 0.000 was discovered. To remedy these problems, the study revealed that prompt payment for executed works, predicting market price fluctuation and inculcating it into the initial estimate, and owner’s involvement at the planning and design phase are some of the possible measures to be adopted.